Effect of exogenous elicitors in enhancing the postharvest quality and antioxidant potential of Spinacia oleracea cv. Pusa Jyothi - Menon, Soumya V; Kumar A, Ashrith; Rai, Priyanka; Ahamed, O M J Afzal (Journal of Postharvest Technology, 2023)
The effect of exogenous elicitors such as methionine and salicylic acid on spinach were investigated in the current study. Leaves were  treated with 100, 200 µM of salicylic acid and 10 and 50mM of methionine as elicitors. Complete retention of chlorophylls was possible in  the spinach treated with 200 µM of salicylic acid. The shelf life of spinach was increased up to 9 days in comparison with the control which  deteriorated in 5 days of storage at 15℃. Both the treatments were effective in improving the phenolic and antioxidant potential of spinach  during the storage. The results from the present study highlights the synergetic effect of elicitors in extension of shelf life and quality of the  spinach. In future, strategies can be developed based on the effect of these elicitors, especially salicylic acid on improvement of postharvest  quality of fruits and vegetables.
Keywords: Antioxidant; ascorbic acid; elicitors; methionine; postharvest losses,; salicylic acid; spinach; storage